Implementation of Legal Protection for Victims of Human Trafficking as Online Gambling Admins in Law Enforcement Practices in Indonesia - Subhan Lubis, Citra; Rahmayanti; Ramadani, Suci (International Conference Epicentrum of Economic Global Framework, 2026)
This study examines the application of legal protection for victims of human trafficking who are exploited as online gambling admins in law enforcement practices in Indonesia. The main issue examined is the status of victims who may appear to be involved in online gambling activities, but may substantively be deceived, coerced, threatened, held captive, controlled, or exploited by human trafficking networks. This study aims to analyze the forms of legal protection for victims, their application in the law enforcement process, and the obstacles that arise in distinguishing victims from the main perpetrators. The research method used is normative juridical with a statutory and conceptual approach, through a review of legal provisions regarding human trafficking, online gambling, witness and victim protection, and restitution for victims of criminal acts. The results of the study indicate that legal protection for victims must be implemented from the stages of investigation, inquiry, prosecution, trial, and post-case recovery. This protection includes victim identification, prevention of criminalization, legal assistance, security protection, identity confidentiality, rehabilitation, restitution, repatriation, and social reintegration. The main obstacles in its implementation include the difficulty of proving exploitation, the dominant criminal approach to online gambling, weak inter-institutional coordination, and the organized and transnational nature of the crime. Therefore, law enforcement needs to adopt a victim-centered approach so that victims of human trafficking are not punished as perpetrators but rather protected as those who have lost their free will due to exploitation.